The Influence of Parenting Style on the Formation of Disciplinary Character of Cadets: Literature Review - Untung Lestari Nur Wibowo; Daniel Dewantoro Rumani; Arief Rusdyansyah; Cris Kuntadi (Dinasti Publisher, 2023)
The purpose of this literature review is to explore the influence of parenting patterns on character formation towards the discipline of cadets. The parenting pattern applied plays a crucial role in the formation of cadet discipline. Strong discipline is one of the key factors in a cadet's success in facing tasks and challenges. Scientific articles from various sources were accessed and analyzed to identify the parenting patterns that influence cadet discipline. The research results show that a democratic parenting pattern has a positive influence if applied in the family environment. In the context of transportation vocational schools, the application of a democratic parenting pattern can be applied to help cadets build confidence, and develop leadership skills, and independence. Meanwhile, the application of an authoritarian parenting pattern can be done by providing clear rules and firm actions to shape discipline and responsibility.